Effect of Auxins on Adventitious Rooting from Hardwood Cuttings of Hippophae Rhamnoides under Ladakh Himalayas - Janifer Raj, X.; Ballabh, Basant; Murugan, M. Pal; Dhar, Priyanka; Tayade, Amol B.; Warghat, Ashish R.; Chaurasia, O. P.; Srivastava, R. B. (Indian Forester, 2013)
The rooting response of hardwood cuttings of Seabuckthorn (Hippophae rhamnoides) treated with auxins was studied during 2008-2009 to standardize the vegetative propagation. The effect of rooting hormones was observed for number of shoots, and roots, maximum length of primary root and rooting percentage. The results indicated that the dip application of 300 ppm IBA for 48 hours was optimum for treating the hardwood cuttings of Hippophae rhamnoides taken in March and will be beneficial for its successful propagation and cultivation under Ladakh Himalaya conditions.